2020
DOI: 10.1128/aem.02425-19
|View full text |Cite|
|
Sign up to set email alerts
|

Pigmentiphaga sp. Strain D-2 Uses a Novel Amidase To Initiate the Catabolism of the Neonicotinoid Insecticide Acetamiprid

Abstract: Acetamiprid, a chloronicotinyl neonicotinoid insecticide, is among the most commonly used insecticides worldwide, and its environmental fate has caused considerable concern. The compound 1-(6-chloropyridin-3-yl)-N-methylmethanamine (IM 1-4) has been reported to be the main intermediate during acetamiprid catabolism in microorganisms, honeybees, and spinach. However, the molecular mechanism underlying the hydrolysis of acetamiprid to IM 1-4 has not yet been elucidated. In this study, a novel amidase (AceAB) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Both pathways produce 6-chlorofluorocarbic acid and 6-phosphatebased phosphoric acid, which are easily degradable organic substances that are oxidized to produce H 2 O and CO 2 [77]. Amidase and its encoding genes, such as aceA and aceB, play a leading role in imidacloprid degradation [78].…”
Section: Neonicotinoid Insecticide Degradation Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Both pathways produce 6-chlorofluorocarbic acid and 6-phosphatebased phosphoric acid, which are easily degradable organic substances that are oxidized to produce H 2 O and CO 2 [77]. Amidase and its encoding genes, such as aceA and aceB, play a leading role in imidacloprid degradation [78].…”
Section: Neonicotinoid Insecticide Degradation Pathwaymentioning
confidence: 99%
“…Agrochemicals 2024, 3, FOR PEER REVIEW 7 to produce H2O and CO2 [77]. Amidase and its encoding genes, such as aceA and aceB, play a leading role in imidacloprid degradation [78]. As research progresses, the pathways of acetamiprid biodegradation are better understood (Figure 2).…”
Section: Neonicotinoid Insecticide Degradation Pathwaymentioning
confidence: 99%
“…Gene cloning and overexpression related studies proved that a nitrile hydratase mediated acetamiprid hydration to IM-1-2. Yang H. et al (2020) studied the enzymatic degradation pathway of acetamiprid using the Pigmentiphaga sp., facilitated by nitrile hydratase. Additionally, amidase and its encoding genes such as aceA and aceB are used for effective degradation.…”
Section: Molecular Approachesmentioning
confidence: 99%
“…Biodegradation genomics is used to identify effective genes in various microbial communities that encode specific enzymes used in biodegradation ( Bharagava et al, 2019 ). Recently, Yang H. et al (2020) identified novel amidase enzymes and genes from Pigmentiphaga sp. strain D-2 by using genomics tools involved in the degradation of acetamiprid.…”
Section: Microbial Technologies For the Enhanced Neonicotinoid Biodegradationmentioning
confidence: 99%
“…Pigmentiphaga strains are common inhabitants of polluted soil, activated sludge, and wastewater, and possess versatile metabolic capabilities for environmental pollutants, such as phenanthrene, aniline, acetamiprid, benzoxazolinone, and fenoxaprop‐ethyl (Blümel & Stolz, 2003; Dong et al, 2015; Dong et al, 2016; Dong et al, 2018; Huang et al, 2018; Li et al, 2018; Wang et al, 2013; Yang et al, 2020). In our previous study, a 3,5‐dibromo‐4‐hydroxybenzoate (DBHB)‐degrading strain of Pigmentiphaga sp.…”
Section: Introductionmentioning
confidence: 99%